Development and user evaluation of an online caregiver education resource for Malaysian parents of children with leukemia or lymphoma - Tan, Chai-Eng; Admodisastro, Novia; Lau, Sie Chong Doris; Tan, Kit Aun; Teh, Kok Hoi; Lee, Chee Chan; Mohd Sidik, Sherina (Asian Onscology Nursing Society, 2024)
Objective: Malaysian parents of children diagnosed with leukemia or lymphoma stand to benefit from a comprehensive Malay-language online resource, complementing existing caregiver education practices. This study aimed to develop and assess the efficacy of e-Hematological Oncology Parents Education (e-HOPE), an online caregiver education resource in Malay, designed to enhance the knowledge of parents with children diagnosed with leukemia or lymphoma in Malaysia. Methods: A user profile and topic list were established based on previous needs analysis studies. Content was developed for each identified topic. An expert panel assessed the content validity of both informational content and activity sections. Subsequently, the contents were presented via a learning management system to parents of children newly diagnosed with leukemia or lymphoma. Parents evaluated the quality of e-HOPE using the Website Evaluation Questionnaire (WEQ) after an 8-week period. Results: The scale content validity index (S-CVI/Ave) achieved 0.996 for informational content and 0.991 for the activity section. Sixteen parents provided evaluations of e-HOPE after an 8-week usage period. Mean WEQ scores for various dimensions ranged from 4.23 for completeness to 4.88 for relevance. Conclusions: E-HOPE was meticulously designed and developed to offer Malaysian parents a Malay-language resource complementing current caregiver education practices. It exhibited strong content validity and received positive user ratings for quality. Further assessment is warranted to evaluate its effectiveness in supporting parents of children with leukemia or lymphoma. The resource is anticipated to enhance information accessibility and support for Malaysian parents facing hematological cancers in their children. Trial registration: Clinicaltrials.gov NCT05455268. © 2023 The Author(s)